FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN TEH CELUP BUNGA TELANG (Clitoria ternatea. L) DAN TEH PUTIH (Camellia sinensis) - Eko Sri Wahyuningsih; Farida Nur Aeni; Farhamzah Farhamzah; Neni Sri Gunarti (Jurnal Buana Farma, 2024)
if there is an increase in free radicals in an uncontrolled amount, more antioxidants are needed to minimize and neutralize the effects of free radicals. These antioxidants can come from consumed food ingredients such as tea bags with a combination of butterfly pea flowers (Clitoria ternatea. L) and white tea (Camellia sinensis) because they have the potential to provide protection from free radicals that can damage body cells. The aim of the study was to determine the levels of antioxidants that would be obtained from combining plants that have high antioxidant activity into a preparation in the form of tea bags. The method used is in vitro using UV-Vis spectrophotometry. Testing of antioxidant activity using the DPPH (1,1-Diphenyl- 2-Picrilhydrazyl) method and data analysis using the Kruskal Walls non-parametric test. In this study the results showed that butterfly pea flowers contain alkaloid compounds, flavonoids, saponins, quinones, and tannins, as well as white tea which contains alkaloids, flavonoids, saponins, quinones, and tannins. The antioxidant activity of butterfly pea flower produced an IC50 value of 262.778 ppm, white tea produced an IC50 value of 14.091 ppm, and formulations of butterfly pea flower and white tea bags that had potential as antioxidants were F1 with an IC50 value of 16.510 ppm. Preparations of teabags of butterfly pea and white tea with a concentration ratio of 50% : 50% are effective as antioxidants and are the preferred formula based on hedonic tests which include color, smell and aroma of teabag preparations.